SENTIMENT ANALYSIS IN SOCIAL NETWORKS USING NAiVE BAYES ALGORITHM - MAHMOUD, MOHAMED YAHYA (Universiti Teknologi Petronas, 2011)
This report is concerned with the opinion mining and sentiment analysis in social networks especially Twitter, it aims to give a brief insight into the ongoing research in sentiment analysis algorithms and techniques, and graphical representation of the statistical results by applying the sentiment analysis on social networks. The objectives of this project is to perform a detailed research on the latest techniques in the process, and to enhance the current approaches of sentiment analysis by building a tool with an ability to provide statistical information, graphically represented -to an acceptable degree of accuracy- to show the collective consciousness of Internet users. The implementation of this project will most probably use third party tools available on the web to reduce time needed and for rapid prototyping in the initial stages of implementation.